Emotional Intelligence from the Perspective of the Qur’an: Its Relevance to Contemporary Islamic Education - Hasan, M Apip; Maulida, Shofia (FKIP - Universitas Riau, 2025)
This study aims to explore the concept of emotional intelligence from the perspective of the Qur'an and its relevance in contemporary Islamic education. The research employs a qualitative method with a library research approach, referring to primary sources such as the Qur'an and hadith, supported by secondary sources including books and scholarly journals. The findings reveal that Qur'anic values related to emotional intelligence, such as self-control, empathy, self-motivation, and building harmonious relationships, are highly relevant in shaping students' character. These values not only support intellectual development but also enhance learners' emotional and spiritual dimensions. The implication of this research is the importance of integrating Islamic-based emotional intelligence into the educational curriculum. Such integration plays a crucial role in producing a generation that excels intellectually, emotionally, and spiritually, and is capable of facing the challenges of the modern era. Therefore, Islamic education must adopt a holistic approach that includes emotional intelligence as a vital component of the learning process.